An analysis of BMPM photojournalism and its impact to Negros Traditional Journalists - Bastian, Liezal Margie Lou S.
This research is geared towards identifying the visual elements that make BMPM photojournalism as either a catalyst or a threat according to Negros traditional journalists, specifically in determining if the values required for traditional media to become newsworthy be likewise applied to Bayan Mo I-Patrol Mo (BMPM)?s photojournalism when comparatively analyzed. It assesses if Negros traditional journalists are in approval or disapproval of BMPM as a citizen journalism platform especially during typhoon Yolanda. This study is carried in order to further understand BMPM?s implications, as a social-media based citizen journalism platform, to the society. A content analysis wherein Typhoon Yolanda-related BMPM photos submitted form November 8 up to December 8 are analyzed and a survey answered by Negros Press Club members selected through Systematic Random Sampling were conducted. Content analysis results showed that catalyst visual elements prevail more than its threat counterpart, signifying that traditional news values are dominantly applied in BMPM photos. On the other hand, survey results have shown that Negros traditional journalists viewed that BMPM photojournalism contains visual elements of threat. Furthermore, they disapproved BMPM as a citizen journalism platform because it can reduce the quality of journalism disseminated to the public due to the uncertainty of Bayan Patroller?s lack of formal background in journalism.